Cost and Benefit Analysis of Different Buildings Through Reuse of Treated Greywater - Elif Ayyüce Kılınç; Erdem Görgün; Aysegul Tanık; Asude Hanedar (Journal of Advanced Research in Natural and Applied Sciences)
The fact that the impacts of climate change cannot be prevented in the short term has increased the importance of climate change adaptation activities, and many national and international studies have been initiated in this regard. Greywater reuse (GWR) activities have become important methods recommended by the Intergovernmental Panel on Climate Change (IPCC) for adaptation to climate change. This study selects GWR from 3 different real typologies, a hotel, a residential building, and an industrial plant planned in Izmir Province of Türkiye, to design greywater systems followed by cost-benefit analyses. The applicability of GWR systems in these typologies has been analyzed, and comparisons have been made. GWR systems at the project design stage eliminate the need for installation modifications. Therefore, it is concluded that new buildings should be designed to integrate these alternative water resource systems. Recovered water through the installation of GWR systems is recommended to be used as flushing water, and the excess for garden irrigation, car washing and cleaning. The payback periods were calculated as 12 years for the hotel and industrial plant and 6 years for the residential building. The water savings were calculated as 46% for the hotel, 44% for the residential building, and 29% for the industrial plant. The results put forth the feasibility of this alternative water resource.